Synthesis of Magnetic-Nanoparticle/Ansamitocin Conjugates-Inductive Heating Leads to Decreased Cell Proliferation In Vitro and Attenuation Of Tumour Growth In Vivo - Seidel, Katja; Balakrishnan, Asha; Alexiou, Christoph; Janko, Christina; Komoll, Ronja-Melinda; Wang, Liang-Liang; Kirschning, Andreas; Ott, Michael (Chemistry - A European Journal, 2017)
Conjugates based on nanostructured, superparamagnetic particles, a thermolabile linker and a cytotoxic maytansinoid were developed to serve as a model for tumour-selective drug delivery and release. It combines chemo- with thermal therapy. The linker-modified toxin was prepared by a combination of biotechnology and semisynthesis. Drug release was achieved by hyperthermia through an external oscillating electromagnetic field that induces heat inside the particles. Efficacy of this release concept was demonstrated both for cancer cell proliferation in vitro, and for tumour growth in vivo, in a xenograft mouse model. Biocompatibility studies for these magnetic-nanoparticle/ansamitocin conjugates complement this work.
EVALuna2:33212